Environmental impacts of urban sprawl in Londrina, Paraná, Brazil - Polidoro, Maurício; de Lollo, José Augusto [UNESP]; Barros, Mirian Vizintim Fernandes (Journal of Urban and Environmental Engineering, 2011)
Public policies encouraging the insertion of large industrial and commercial developments near highways, associated to exclusionary housing policies, have shaped over the past decades a new urbanization phenomenon; the sprawl. This is largely characterized by discontinuous and fragmented occupation, with random population densities. This phenomenon brings environmental and social impacts to the urban and rural population, in addition to a great burden for the Government. In line with this and considering the lack of discussion about the topic, this paper discusses some of those impacts observed in Londrina - PR, Brazil. The influence of urban sprawl in this city has shown to impact traffic, waterproofing rates and green areas, in addition to underutilizing the infrastructure due to large urban voids and vacant lots. With the data presented here, it is hoped that debates emerge on the importance of rethinking the plan, so that everyone can have legal access to the city (endowed with infrastructure), as well as the importance of developing strategies to contain urban sprawl. © 2011 Journal of Urban and Environmental Engineering (JUEE). All rights reserved.
Keywords: Impacts; Londrina; Urban planning; Urban sprawl